2010
DOI: 10.1002/mds.23374
|View full text |Cite
|
Sign up to set email alerts
|

Central oscillators in a patient with neuropathic tremor: Evidence from intraoperative local field potential recordings

Abstract: Present pathophysiological concepts of neuropathic tremor assume mistimed and defective afferent input resulting in deregulation of cerebello-thalamo-cortical motor networks. Here, we provide direct evidence of central tremor processing in a 76-year-old female who underwent bilateral deep brain stimulation of the ventral intermedial nucleus of the thalamus (Vim-DBS) because of neuropathic tremor associated with IgM paraproteinemia. Electrophysiological recordings of EEG and EMG were performed in three perioper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
(17 reference statements)
1
18
0
1
Order By: Relevance
“…These results confirmed that motor brain processing was significantly altered in individuals with CP as it occurs in other movement disorders (Graziadio et al, 2012;Muthuraman et al, 2010;Weiss et al, 2012Weiss et al, , 2010Fang et al, 2009). Corticomuscular coherence is thought to reflect the functional coupling between motor cortex and muscle motor units during motor performance (Mima and Hallett, 1999).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These results confirmed that motor brain processing was significantly altered in individuals with CP as it occurs in other movement disorders (Graziadio et al, 2012;Muthuraman et al, 2010;Weiss et al, 2012Weiss et al, , 2010Fang et al, 2009). Corticomuscular coherence is thought to reflect the functional coupling between motor cortex and muscle motor units during motor performance (Mima and Hallett, 1999).…”
Section: Discussionsupporting
confidence: 70%
“…Finally, some studies have revealed that corticomuscular coherence is affected by changes in descending drive from spinal and cortical levels. Thus, for instance, corticomuscular coherence has proven to be altered in healthy individuals after inmobilization (Lundbye- Jensen and Nielsen, 2008) or in neurological conditions such as essential (Muthuraman et al, 2010) and neuropathic tremor (Weiss et al, 2010), Parkinson disease (Weiss et al, 2012), stroke (Graziadio et al, 2012;Fang et al, 2009) or pseudo-choreoathetosis (Timmermann et al, 2001). Nevertheless, there is currently no data about the effects of cerebral palsy on corticomuscular coherence.…”
Section: Introductionmentioning
confidence: 96%
“…Two studies reported no occurrence of AEs, and 2 studies did not report AEs. Stimulation frequency varied from 130 to 185 Hz, intensity from 0.6 to 4.5 V, and pulse width from 60 to 210 sec (Table 4) [12, 7581]. …”
Section: Resultsmentioning
confidence: 99%
“…Central oscillators have also been implicated in generation of neuropathic tremor . Specifically, deep brain stimulation studies have suggested the importance of the ventral intermediate nucleus (VIM) of the thalamus, whereby stimulation of the VIM results in a significant reduction of neuropathic tremor.…”
Section: Discussionmentioning
confidence: 99%